2023
DOI: 10.1101/2023.10.04.23296554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain-targeted autoimmunity is strongly associated with Long COVID and its chronic fatigue syndrome as well as its affective symptoms

Abbas F. Almulla,
Michael Maes,
Bo Zhou
et al.

Abstract: BackgroundAutoimmune responses contribute to the pathophysiology of Long COVID, affective symptoms and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS).ObjectivesTo examine whether Long COVID, and its accompanying affective symptoms and CFS are associated with immunoglobulin (Ig)A/IgM/IgG directed at neuronal proteins including myelin basic protein (MBP), myelin oligodendrocyte glycoprotein (MOG), synapsin, α+β-tubulin, neurofilament protein (NFP), cerebellar protein-2 (CP2), and the blood-brain-bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Similarly, antibodies against SARS-CoV-2 superantigen, HHV-6 U24, and HHV-6 dUTPase, MBP, MOG, NFP, synapsin, cerebellar protein-2, and tubulin were measured using enzymelinked immunosorbent assay (ELISA) as explained previously [15,18].…”
Section: Assaysmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, antibodies against SARS-CoV-2 superantigen, HHV-6 U24, and HHV-6 dUTPase, MBP, MOG, NFP, synapsin, cerebellar protein-2, and tubulin were measured using enzymelinked immunosorbent assay (ELISA) as explained previously [15,18].…”
Section: Assaysmentioning
confidence: 99%
“…In their study, Almulla et al [18] found that heightened autoimmune responses, specifically those mediated by IgG and IgM to neuronal antigens, play a significant role in the development of Long COVID and the emergence of new affective and CFS symptoms. Some of the proteins mentioned in the study are myelin basic protein (MBP), myelin oligodendrocyte glycoprotein (MOG), neurofilament light (NFL), synapsin, tubulin, cerebellar protein-2, and the blood-brain barrier (BBB) proteins claudin-5 and S100B [18]. Thus, it can be inferred that infection with the SARS-CoV-2 virus has the potential to reactivate dormant viruses.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent studies, however, have identified key factors contributing to these conditions. Notably, evidence points to increased neuroimmune-inflammation, oxidative and nitrosative stress (Al-Hakeim et al, 2022 ), persistent SARS-CoV-2 infection (Vojdani et al, 2023 ), and autoimmune reactions (Almulla et al, 2023b ). These findings have spurred the construction of the current Research Topic encompassing articles, reviews, and case reports, aimed at deepening our understanding of the biological mechanisms driving psychiatric and neurodegenerative comorbidities in acute and Long COVID.…”
mentioning
confidence: 99%